SHALLOT FARMING PRODUCTIVITY AND FARMER INCOME AFFECTED BY WATER RESOURCES DISTANCE IN WANASARI - Btari Sukmastika Hemas; Siswanto Imam Santoso; Wiludjeng Roessali (Tadulako University, 2019)
Shallot farming productivity refers to the ecosystem supporting. This study aims to analyze the difference between productivity and income of shallot farming based on the distance from the water resources. Additionally, factors that affected the farmer's income were also studied with a survey approach by using purposive sampling in Wanasari District, Brebes Regency. The data collected through interviews with the questionnaire. The data were analyzed by using productivity analysis, income analysis, Kruskal-Wallis Test, and multiple linear regression analysis. The results showed that there was a difference in farmer's productivity and income based on the distance to the water resources. The productivity of shallot in Wanasari District amounts to 12,780 kg/ha/planting season. Meanwhile, the farmer's income in Wanasari District amounted to IDR 57,677,334/ha/planting season. According to the data analysis, factors that affect the shallot farmers' income were shallot price, productivity, the amount of TSP and NPK fertilizers, and the amount of pesticide applied.